Analisis Implementasi Sistem Informasi Akuntansi Dalam Meningkatkan Kinerja Operasional Perumda Air Minum Mual Nauli - Rambe, Masril Tua; Surianti, Meily; Deliana, Deliana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The purpose of this study is to evaluate the contribution of Accounting Information System (AIS) implementation to Operational Performance at Perumda Air Minum Mual Nauli and to understand changes in the company’s condition following the system’s adoption. This research uses a comparative method with a qualitative approach, conducted at Perumda Air Minum Mual Nauli, located on Jalan Adonia Hutagalung No. 01, Sibuluan Raya Village, Pandan District, Central Tapanuli Regency, North Sumatra. Data collection was carried out through direct observation, in-depth interviews with relevant informants, and documentation related to the implementation. The results show that the AIS implementation significantly contributed to improving the company's operational performance, evidenced by timely availability of information, improved information quality, streamlined business processes, more efficient inventory management, and timely deliveries. Following the implementation of the Accounting Information System, Perumda Air Minum Mual Nauli demonstrates operational and efficiency improvements.